Grease and its Application on Electrical Equipment: a Review - Suhaila A Japar, N; Aizudin A. Aziz, M; Najib Razali, Mohd; Waheeda Abdu Rahman, Nurul; ., . (International Journal of Engineering and Technology, 2018)
Grease hardening and dry-out have been part of the major challenges in grease usage in electrical industry. The findings obtained over the years related to the study of synthetic, specialty, and new grease have found that the usage of these greases are costly; hence, it is very necessary to find an alternative method to reduce the cost as much as possible. Increasing petroleum demands, depletion of petroleum reserves, and the environmental awareness have influenced a huge interest in the use of waste oil as the alternative of base oil for grease formulation. The waste oils are considered as a promising candidate due the fact that the re-refining process of base oil is relatively cheap with high yield and the recovery of good quality oil. Optimum grease formulation is necessary in solving the aforementioned issues as well as overcoming complication specifically in the electrical industry where these greases are mainly utilized.Â Â